Alkenylboronic Ester Activation to Nucleophilic Addition and Electrophilic Trapping with Carbonyl Groups - González, Sara; Fernández, Elena (Synlett, 2022)
Carbolithiation of (1-phenylvinyl)boronic acid pinacol ester with tert-butyllithium was used to generate α-phenylboryl carbanions that reacted in a straightforward manner with carbonyl groups through a boron–Wittig sequence. When unhindered α,β-unsaturated carbonyl compounds were used, 1,4-addition of the α-phenylboryl carbanions was observed over the boron–Wittig sequence.
Keywords: alkenylboronates; alkylideneboranes; boron–Wittig reaction; boron ate suppression; boryl carbanions